Amplitude modulated Lorentz force MEMS magnetometer with picotesla sensitivity. (20th September 2016) - Kumar, Varun; Ramezany, Alireza; Mahdavi, Mohammad; Pourkamali, Siavash
Abstract: This paper demonstrates ultra-high sensitivities for a Lorentz force resonant MEMS magnetometer enabled by internal-thermal piezoresistive vibration amplification. A detailed model of the magneto-thermo-electro-mechanical internal amplification is described and is in good agreement with the experimental results. Internal amplification factors up to 1620 times have been demonstrated by artificially boosting the effective quality factor of the resonator from 680 to 1.14 × 10 6 by tuning the bias current. The increase in the resonator bias current in addition to the improvement in the quality factor of the device led to a sensitivity enhancement by 2400 times. For a bias current of 7.245 mA, where the effective quality factor of the device and consequently the sensitivity is maximum (2.107 mV nT −1 ), the noise floor is measured to be as low as 2.8 pT (√Hz) −1 . This is by far the most sensitive Lorentz force MEMS magnetometer demonstrated to date.